Combining Terrestrial Laser Scanning and Drone-Based Photogrammetry towards Improving Volume Calculations in Construction Projects - Sharafaddin Th. Muhammed; Fanar M. Abed (Journal of Engineering, 2025)
This research aims to co-register UAV (Unmanned Aerial Vehicle) photogrammetry and Terrestrial Laser Scanning (TLS) for volumetric measurements of irregularly shaped material stacks available at construction sites in Iraq. The research investigates the potential of combining these techniques in comparison to standalone and traditional techniques to improve volume quantification and time consumption. An area containing a stockpile of bulk materials and building remnants was selected. A low-cost drone was used for data acquisition, whereas Structure from Motion (SFM) and Multi View Stereo (MVS) algorithms were used for processing and analysing the photogrammetric data. In contrast, Stonex X300 TLS device was used for laser data collection, while 3D Re-constructor software was used for data processing and analysis. The resulting volume from utilizing individual techniques came out as follows: 2692 m3 from UAV photogrammetry with an accuracy of ±6 mm, 2730.99 m3 from integrating photogrammetry and TLS with an accuracy of ±35 cm, while the conventional approach delivers 3048 m3 with an accuracy of ±1.1 cm. The data integration (fusion) approach shows a high error level due to data registration obstacles, which can be overcome if the target-based registration approach is applied to increase the accuracy level to several millimeters. In this research, the results indicate the significant effectiveness of low-cost drones to deliver accurate volume measurements in photogrammetry, which outperform the conventional techniques for estimation, management, and precise volume calculation of the stocks and materials in construction projects. This was approved in the perspective of time, data intensity, cost effectiveness, and labor intensity following data analysis.